2019
DOI: 10.1186/s12909-019-1495-0
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum management/monitoring in undergraduate medical education: a systematized review

Abstract: Background Monitoring and management of undergraduate medical education (UME) curricula are crucial contributors to successful medical education. This systematized review explores the different approaches that medical schools have to UME curriculum management or monitoring in order to provide a basis for curriculum managers. Methods PubMed, Science Direct, Scopus, and ERIC were searched with no time limitation using the keywords curriculum , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
(56 reference statements)
0
14
0
5
Order By: Relevance
“…Regular assessment, feedback, and monitoring of the undergraduate curriculum of psychiatry are the fundamental work for the development of psychiatry in a country. [ 8 ] This review was aimed to assess the undergraduate psychiatry curriculum of four LMICs of South-East Asia (Bangladesh, India, Nepal, and Sri Lanka) [ Table 1 ]. The study revealed wide variations in allocation of time and place in psychiatry at the undergraduate level among the four countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regular assessment, feedback, and monitoring of the undergraduate curriculum of psychiatry are the fundamental work for the development of psychiatry in a country. [ 8 ] This review was aimed to assess the undergraduate psychiatry curriculum of four LMICs of South-East Asia (Bangladesh, India, Nepal, and Sri Lanka) [ Table 1 ]. The study revealed wide variations in allocation of time and place in psychiatry at the undergraduate level among the four countries.…”
Section: Discussionmentioning
confidence: 99%
“…A curriculum is a basic structure of any degree, and the quality of its implementation brings the output. [ 8 ] Hence, there is a need for a comparable and compatible curriculum in medical education among these countries. While the curricula in the region should address the specific educational issues arising from the shared sociocultural factors, in the setting of globalization, it is important that these curricula attempt to meet the international standards of medical education as well.…”
Section: Introductionmentioning
confidence: 99%
“…Developing a CM, requires careful consultation, planning, building and curation [30,31]. Specifically, determining the level of detail and complexity is vital as this has implications for costs, staffing and ongoing running.…”
Section: Why Develop a Curriculum Map At Uclms?mentioning
confidence: 99%
“…Ante la situación planteada y con el objetivo de mantener la calidad educativa, las universidades llevan a cabo procesos de evaluación curricular que les permiten fundamentar la toma de decisiones para el rediseño de planes de estudio. Es decir, ejercicios participativos con el fin de obtener información sobre las fortalezas y debilidades de los elementos curriculares de los PE, con la finalidad de interpretarla (Alexander y Hjortsø, 2019;Changiz et al, 2019;Glatthorn et al, 2019). Asimismo, para lograr la calidad educativa se requieren procesos de diseño curricular reflexivos que favorezcan la articulación de los tres niveles de concreción curricular.…”
Section: Introductionunclassified